Pertanggung Jawaban Pidana terhadap Prajurit TNI yang Melakukan Penyalah Gunaan Wewenang Jabatan dalam Perspektif Negara Hukum - Joko Tri Suhartono; Budi Pramono; Agung Pramono (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
Abuse of official authority by Indonesian National Armed Forces (INAF) soldiers is a legal issue that is not only related to criminal liability, but also concerns the principles of the rule of law, judicial independence, and the protection of human rights. This study aims to analyze the conformity of the law enforcement process against INAF soldiers who commit abuse of official authority with the principles of the rule of law and examine the correlation between military criminal law and state administrative law from the perspective of detournement de pouvoir. The study uses a normative legal method with a statutory, conceptual, case, and comparative approach. Legal materials were obtained through library studies that include laws and regulations, court decisions, scientific literature, and other supporting documents, then analyzed qualitatively through legal interpretation and juridical analysis. The results of the study indicate that although the regulations regarding the criminal liability of INAF soldiers have a clear legal basis, their implementation does not fully reflect the principles of the rule of law. Problems are still found in the aspects of the independence of investigators, prosecutors, and military judges, the connectivity mechanism, and the orientation of jurisdiction that is based more on the status of the perpetrator than the character of the crime. This study also found that the concept of detournement de pouvoir provides a meeting point between military criminal law and state administrative law in assessing abuse of office. Therefore, military justice reform, strengthening the independence of law enforcement officials, and harmonizing legal regulations are needed to achieve transparent, accountable law enforcement that aligns with the principles of equality before the law, fair trial, and human rights protection.